Horrible Harry and the green slime - Kline, Suzy.; Remkiewicz, Frank (New York, N.Y., U.S.A. : Puffin Books, 1991)
Follows the school activities of second-graders, Harry and Doug, as they participate in a secret mission to celebrate "Charlotte's Web," learn how to make green slime, and put on a skit warning about the dangers of smoking.
Booklist
School Library Journal
3.3
3-6
Keywords: Schools -- Fiction; Friendship -- Fiction; Friendship -- Fiction; School stories